Mechanistic MALDI-TOF Cell-Based Assay for the Discovery of Potent and Specific Fatty Acid Synthase Inhibitors. Issue 9 (19th September 2019) - Weigt, David; Parrish, Cynthia A.; Krueger, Julie A.; Oleykowski, Catherine A.; Rendina, Alan R.; Hopf, Carsten
Summary: Human cancers require fatty acid synthase (FASN)-dependent de novo long-chain fatty acid synthesis for proliferation. FASN is therefore an attractive drug target, but fast technologies for reliable label-free cellular compound profiling are lacking. Recently, MALDI-mass spectrometry (MALDI-MS) has emerged as an effective technology for discovery of recombinant protein target inhibitors. Here we present an automated, mechanistic MALDI-MS cell assay, which monitors accumulation of the FASN substrate, malonyl-coenzyme A (CoA), in whole cells with limited sample preparation. Profiling of inhibitors, including unpublished compounds, identified compound1 as the most potent FASN inhibitor (1 nM in A549 cells) discovered to date. Moreover, cellular MALDI-MS assays enable parallel profiling of additional pathway metabolites. Surprisingly, several compounds triggered cytidine 5'-diphosphocholine (CDP-choline) but not malonyl-CoA accumulation indicating that they inhibit diacylglycerol generation but not FASN activity. Taken together, our study suggests that MALDI-MS cell assays may become important tools in drug profiling that provide additional mechanistic insights concerning compound action on metabolic pathways. Graphical Abstract: Highlights: Proof-of-concept for label-free automated MALDI-MS-based mechanistic cell assay Characterization of most potent fatty acid synthase inhibitor (1 nM in A549 cells) MALDI-MS-based profiling identifies metabolite marker of lipid synthesis inhibition Abstract : The study by Weigt et al. adds robust, fast, label-free mechanistic MALDI-MS-based cell assays to the chemical biology toolbox. These assays can support compound screening and profiling, and they monitor multiple metabolite markers in parallel. Being reagent independent, they may eventually enable studies of currently intractable targets directly in cells.